Model of Fable Text Story Containing Attitude and Moral in Language in Literature Course at Faculty of Language and Literature, Universitas Negeri Medan - Rosmawaty Rosmawaty; Rosdiana Siregar; Sumarsih Sumarsih (BIRCU, 2022)
The use of language in speaking will show how a person's attitude is in using his own language or others language when someone is in the process of communicating (speaking). Freedom of language can be seen from his/her attitude of the language. The language used should be seen in its context, for example in literature. The literature context is written with various characteristics, they are in terms of content, expression and beauty. Literature work is the results of an imagined human creation. One of them is a fable story. This fable story is a story about human life whose characters are animals that the behavior resembles humans. This study focuses on the model of fable text story and its effect on the improvement in attitude and moral in language of Indonesian Language Study Program students at the Faculty of Language and Arts, Universitas Negeri Medan. Therefore, theoretically and practically, this research is expected to be able to contribute. Theoretically, this research contributes as a reference in science, they are the model of fable story which contains attitudes and moral in language in the Literature course at FBS Unimed. Practically, the findings of this study will be useful for: government, Indonesian language teachers, and any other research. The stages of this research were conducted with a preliminary stage, and evaluation by using a research and development design. This method is a research method that uses to produce products and test the effectiveness of the products (Sugiono, 2010). The research results are reputable scientific publication articles in the form of indexed journal or proceeding or web of science, final reports that registered with copyright, and a model of fable text story in the KI form (patent or simple patent or copyright, or industrial product design). As an additional output, it is as a mandatory result and a speaker of international scientific seminars.